Authority List of Writers in Telugu Language - Sharada, B. A.; Chetana, M. (Journal of Information and Knowledge, 2005)
This study tries to find a solution for the practical problems involved in rendering Indic names while cataloging with special reference to Telugu books. Based on different methodologies generally applied to select the entry element in the author's name, an Authority list of writers in Telugu is drawn and annexed to this paper. The same problem is tackled in the digital environment also and all the possible ways to retrieve through author search are discussed.